Influence of light spectral ratios on physiological and stomatal parameters of pak choi (Brassica rapa var. chinensis) grown in acontrolled vertical hydroponic system - R, MAHESH; HASAN, MURTAZA; YEASIN, M D; M, RAMYA SREE (The Indian Journal of Agricultural Sciences, 2025)
Light quality, specifically the ratio of red and blue wavelength LEDs, is critical in optimising plants’ photosynthetic rate and related physiological processes for higher yield and quality. The present study was carried out during 2022 and 2023 at ICAR-Indian Agricultural Research Institute, New Delhi to investigate the effects of different red (R) and blue (B) light ratios (R2B1= 2:1, R1B1= 1:1 and R1B2= 1:2) on plants stomatal characteristics and physiological parameters. Significant variations were observed for stomatal pore width, length, and guard cell dimensions across treatments, particularly with R1B1 and control (white light) conditions. Notably, R1B1 demonstrated increased stomatal pore width and guard cell dimensions over time, while control maintained higher stomatal density on the abaxial surface at 30 days after treatment (DAT). Stomatal responses varied, with R2B1 achieving the highest stomatal density and physiological efficiency as evidenced by a net photosynthetic rate of 22.26 µmol CO₂/m²/s and a water-use efficiency (WUE) of 72.67. The control treatment showed the lowest values across all physiological parameters, highlighting the benefits of spectral treatments. Correlation analysis revealed significant positive relationship among the physiological and stomatal parameters, particularly between net photosynthetic rate and WUE (r = 0.97), stomatal conductance and guard cell arc length (r = 0.97). The yield was observed highest (113.61 g fresh weight and 6.98 g dry weight) in R2B1 treatment. These findings underscore the critical role of light quality in optimising stomatal function and enhancing photosynthesis, transpiration and water-use efficiency in plants, suggesting potential applications in controlled agricultural environments.